Twenty Years of Hepatitis C in the Treviso District (Local Health Unit 2): Treatments, Clinical Management and Cost Analysis. (March 2019) - Bellin, Annachiara; Franchin, Giulia; Bolcato, Jenny; Bettiol, Alessandra; Pirolo, Roberta; Schiavon, Alberto; Giusti, Pietro; Tessarin, Michele; Chinellato, Alessandro
Chronic hepatitis C virus (HCV) infection is a global health problem, and about 10-30% of patients develop cirrhosis or hepatocellular carcinoma several years after being infected. In past decades, treatment of HCV infection was based on peginterferon and ribavirin, which lead to a sustained virologic response (SVR) in only 50-60% of patients. Since 2014, direct acting antiviral (DAA) agents have been available. Patients administered DAA agents usually reach SVR in 12 weeks. The aim of this study was to estimate the cost analysis of these innovative drugs while also taking into account the total health expenditure for managing HCV infection. The pharmaceutical and hospitalisation databases of the Local Health Unit (ULSS2) of Treviso were retrospectively analysed between 1997 and 2016 for each HCV patient. During this twenty-year period, people affected by HCV totalled 2, 949; 277 of these patients were treated with DAA and, of these, only 2% did not reach SVR. The HCV genotype 1b was the most common, accounting for 58% of the total patients. The treatment for HCV genotype 3 was associated with higher costs. The expenses for the new treatments were found to be significantly higher compared to those for the old ones (i.e., peginterferon and ribavirin). The average costs for a cycle of therapy were €8, 000 and €24, 000 for interferon and DAA therapy, respectively. Total health care costs associated with HCV (excluding DAA treatments) for an individual HCV infection patient were estimated to be €32, 000. Our results confirm the high efficacy of DAA therapy. Furthermore, these agents improve the clinical conditions and reduce both the treatment cost and health care in patients with HCV infection.